Pancreatitis and atypical Kawasaki disease - Paunovic Zoran; Ristic Goran; Prokic Dragan; Pasic Srdjan (BMC, 2010)
Abstract We report on pediatric patient with clinical and laboratory evidence of pancreatitis at onset of atypical Kawasaki disease (KD). In KD pancreatic inflammation was described previously, but clinical pancreatitis was rarely reported and its true incidence is unknown. In febrile pediatric patients suspected to have KD, but not fulfilling classical diagnostic criteria, signs of pancreatic inflammation may help in making correct diagnosis. Further analysis of cases with atypical KD developing pancreatitis may reveal if signs of pancreatic inflammation can be used as supportive diagnostic finding.